2012
DOI: 10.4012/dmj.2012-005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hardness and fracture toughness, coupled with microstructural analysis, of zirconia ceramics stored in environments with different pH values

Abstract: The aim of this study was to evaluate the effects of pH changes in the oral cavity on the mechanical properties of zirconia and feldspathic ceramics. Bilayered zirconia-feldspathic samples were prepared from three different commercial brands of Y-TZP blocks: Zirkonzahn, Cercon, and Everest. Samples were stored in artificial saliva with different pH values (3.5, 7.0, and 10.0) for 10 days at 37°C. Flexural strength, Vickers hardness, and fracture toughness were calculated after samples were subjected to biaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 36 publications
5
33
0
Order By: Relevance
“…Similar findings were noted in different in vitro studies. 27,34 Our results were similar to those of Etman et al, 5 who quantitatively measured tooth and ceramic wear by using a novel superimposition technique. They reported that the wear of an antagonist tooth against Procera coping with All Ceram (feldspathic porcelain) layering was more in the molar region (184.24 mm) than with another metal ceramic crown with a metal occlusal surface (106.90 mm) and experimental glass ceramic crowns (149.70 mm) after 1 year.…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings were noted in different in vitro studies. 27,34 Our results were similar to those of Etman et al, 5 who quantitatively measured tooth and ceramic wear by using a novel superimposition technique. They reported that the wear of an antagonist tooth against Procera coping with All Ceram (feldspathic porcelain) layering was more in the molar region (184.24 mm) than with another metal ceramic crown with a metal occlusal surface (106.90 mm) and experimental glass ceramic crowns (149.70 mm) after 1 year.…”
Section: Discussionsupporting
confidence: 93%
“…The oral cavity is a dynamic environment where applied force, temperature, and salivary chemistry are constantly changing. These factors may contribute to the well‐known processes of aging often described as a low‐temperature degradation (LTD) phenomenon unique to zirconia . LTD is considered to occur as a spontaneous transformation of the tetragonal to monoclinic phases occurring over time at low temperatures that is not triggered by a local mechanical stress resulting in a lower resistance to fracture …”
mentioning
confidence: 99%
“…These factors may contribute to the well-known processes of aging often described as a low-temperature degradation (LTD) phenomenon unique to zirconia. 9,10 LTD is considered to occur as a spontaneous transformation of the tetragonal to monoclinic phases occurring over time at low temperatures that is not triggered by a local mechanical stress resulting in a lower resistance to fracture. 11 While the literature presents a number of studies to evaluate the mean fracture load of zirconia abutments under varying loading conditions and angulations, limited investigations have considered the combined effects of varied implant angulation on the fracture resistance of zirconia abutments with artificial aging to simulate the structural changes occurring in vivo.…”
mentioning
confidence: 99%
“…One was excluded due to the absence of toughness value. 35 In vitro studies that evaluated the fracture toughness of veneered zirconia, [36][37][38] experimental Y-TZP ceramic, 39,40 or Y-TZP ceramics not obtained from partially sintered blocks, 20,21,[41][42][43] and articles which evaluated HIPped Y-TZP ceramic 44 were excluded. In addition, one article was excluded because it did not have an English translation.…”
Section: Resultsmentioning
confidence: 99%